1997
DOI: 10.1053/jhep.1997.v25.pm0009021948
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived superoxide anion induces lipid peroxidation and stimulates collagen synthesis in human hepatic stellate cells: Role of nitric oxide

Abstract: Hepatic fibrosis is the main histological feature that accomExperimental evidence indicates that the lipid peroxipanies the progression of alcoholic liver injury to cirrhosis dation of biological membranes is often associated with in chronic alcohol abusers. 1,2 Acetaldehyde, a potential prothe development of liver fibrosis. We have studied the oxidant factor linked to ethanol metabolism, has been proeffect of neutrophil-derived reactive oxygen species posed as a mediator of fibrogenesis in alcoholic liver dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 10 publications
2
50
0
2
Order By: Relevance
“…3) suggests that NO and/or downstream RNS protects skeletal muscle from injury caused by neutrophils. This interpretation is in agreement with several in vitro studies which reported a significant protective role of NO against neutrophil-mediated cellular injury (Casini et al 1997;Hansen and Stawski 1994;Murphy et al 1999;Wink and Mitchell 1998). The mechanism for the protection in the present study may be related to NO's ability to inhibit neutrophil adhesion, reduce neutrophilderived ROS production, interrupt lipid peroxidation chain reactions, and/or scavenge other cytolytic molecules (Clancy et al 1992;Kubes et al 1991;Sethi and Dikshit 2000).…”
Section: Contribution Of Rnssupporting
confidence: 93%
“…3) suggests that NO and/or downstream RNS protects skeletal muscle from injury caused by neutrophils. This interpretation is in agreement with several in vitro studies which reported a significant protective role of NO against neutrophil-mediated cellular injury (Casini et al 1997;Hansen and Stawski 1994;Murphy et al 1999;Wink and Mitchell 1998). The mechanism for the protection in the present study may be related to NO's ability to inhibit neutrophil adhesion, reduce neutrophilderived ROS production, interrupt lipid peroxidation chain reactions, and/or scavenge other cytolytic molecules (Clancy et al 1992;Kubes et al 1991;Sethi and Dikshit 2000).…”
Section: Contribution Of Rnssupporting
confidence: 93%
“…These workers believe that hepatic lipid peroxidation associated with ANIT-induced liver injury involves oxygen radicals derived from neutrophils which in®ltrate the liver. Neutrophils are known to mediate lipid peroxidation through the production of superoxide anion via activated NADPH oxidoreductase [Casini et al, 1997]. In the present study histological analyses of liver tissue after ANIT administration showed the in®ltration of neutrophils.…”
Section: Discussionsupporting
confidence: 59%
“…Neutrophils are an important source of ROS, which may have a direct stimulatory effect on HSC collagen synthesis via superoxide. 13 Activated neutrophils also produce NO, which may counteract the effect of superoxide on collagen production but not abrogate it. 13 Endothelial cells are also likely to participate in HSC activation, both by production of cellular fi bronectin and via conversion of TGF-β from the latent to the active, profi brogenic form.…”
Section: Initiationmentioning
confidence: 99%